MENINGKATKAN PEMBELAJARAN GERAK DASAR RENANG DENGAN PENDEKATAN BERMAIN - IKHSAN MAULANA PUTRA; SALI ANDALA (Jurnal Muara Olahraga, 2020)
Some students are not optimal in doing basic swimming movements, because students are passive and not enthusiastic in the learning process, and students still do not understand about basic swimming movements. In addition, the students have not yet taken part in the basic swimming motion learning, due to monotonous learning methods, so students feel that basic swimming motion learning is not fun when compared to soccer and baseball learning, which is much liked by students. The subjects in this research were fifth grade students of SDN 35 / II Seling, Tabir Subdistrict, Merangin Regency with 22 students, 16 male students and 6 female students. The research design used in the form of a cycle that refers to the Kemmis and Mc Taggrat models. This cycle does not only take place once, but several times to achieve the expected goals. This class action research plan, consisting of 2 cycles. Each cycle is carried out in accordance with the changes to be achieved. The purpose of this research is to describe the approach to play can improve the learning process of swimming basic motion and describe the approach to play can improve the learning outcomes of basic swimming motion. Judging from the improvement in the learning process of teachers and improvement of student learning. The results of research on teacher learning in the first cycle obtained the final value of the collaborator assessment of 66.25, teacher learning research in the second cycle obtained the final value of the collaborator assessment of 7.8.